The Escherichia coli thioredoxin homolog YbbN/Trxsc is a chaperone and a weak protein oxidoreductase - Caldas, Thérèse (2006)
Escherichia coli contains two thioredoxins, Trx1 and Trx2, and a thioredoxin-like protein, YbbN, which presents a strong homology in its N-terminal part with thioredoxin 1 and 2. YbbN, however, does not possess the canonical Cys-x-x-Cys active site of thioredoxins, but instead a Ser-x-x-Cys site. In addition to Cys-38, located in the SxxC site, it contains a second cysteine, Cys-63, close to Cys-38 in the 3D model. Cys-38 and Cys-63 undergo an oxidoreduction process, suggesting that YbbN functions with two redox cysteines. Accordingly, YbbN catalyzes the oxidation of reduced RNase and the isomerization of scrambled RNase. Moreover, upon oxidation, its oligomeric state changes from dimers to tetramers and higher oligomers. YbbN also possesses chaperone properties, promoting protein folding after urea denaturation and forming complexes with unfolded proteins. This is the first biochemical characterization of a member of the YbbN class of bacterial thioredoxin-like proteins, and in vivo experiments will allow to determine the importance of its redox and chaperone properties in the cellular physiology.